2019
DOI: 10.1177/1847980419827171
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth controlled reduced graphene oxide–supported palladium electrocatalysts for methanol oxidation reaction

Abstract: In spite of advantages of direct methanol fuel cells, low methanol oxidation reaction and fuel crossover from anode to cathode, there remains a challenge that inhibits it from being commercialized. Active electrocatalysts are in high demand to promote the methanol oxidation reaction. The methanol reached at the anode can be immediately reacted, and thus, less methanol to cross to the cathode. The performance of electrocatalysts can be significantly influenced by varying the concentration of precursor solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Due to the minimal quantity of metal loading on the support material, the crystal plane of Pd (200), (220), and (311) is missing. The diffractogram shows that increasing the amount of metal loading on the support material enhances the intensity of crystallinity while decreasing the crystallite size (CS), as reported by Ng et al [20]. The Scherrer equation is used to obtain these values, which are based on the Scherrer constant (K = 0.9) and the height (H) of the carbon nanostructure.…”
Section: Analysis Of Materials Crystallinitymentioning
confidence: 88%
See 2 more Smart Citations
“…Due to the minimal quantity of metal loading on the support material, the crystal plane of Pd (200), (220), and (311) is missing. The diffractogram shows that increasing the amount of metal loading on the support material enhances the intensity of crystallinity while decreasing the crystallite size (CS), as reported by Ng et al [20]. The Scherrer equation is used to obtain these values, which are based on the Scherrer constant (K = 0.9) and the height (H) of the carbon nanostructure.…”
Section: Analysis Of Materials Crystallinitymentioning
confidence: 88%
“…Furthermore, the peaks near 40° could be attributed to the (111) lattice planes of Pd's face-centered cubic crystalline structure (JCPDS No. 46-1043) [20]. Due to the minimal quantity of metal loading on the support material, the crystal plane of Pd (200), (220), and (311) is missing.…”
Section: Analysis Of Materials Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…1,[7][8][9][13][14][15][16][17] In addition, it should be noted that metalcarbon-polymer nanocomposite films may exhibit interesting pressure-sensitive, catalytic, and gas sensing properties and are promising candidates for the realization of efficient flex, catalytic, and gas sensor devices. [18][19][20][21] In previous studies, we reported on low energy (60 keV) implantation of Cu þ and Ni þ ions in polycarbonate at fluence of 5 Â 10 16 cm À2 and 1 Â 10 17 cm À2 . 14,22 The electrical resistance was reduced considerably and a dependence on the deformation, that is, mechanical-induced strain, was observed proving the potential application of these nanocomposite surface films for the fabrication of strain gauge devices.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 –9,13 –17 In addition, it should be noted that metal–carbon–polymer nanocomposite films may exhibit interesting pressure-sensitive, catalytic, and gas sensing properties and are promising candidates for the realization of efficient flex, catalytic, and gas sensor devices. 18 21…”
Section: Introductionmentioning
confidence: 99%